POWER AND ITS MAIN FACTORS: NON-CONSCIOUS PRIMING OF THE FEELING, STEREOTYPE AND RESPONSIBILITY - Б. Хишигням; Д.Бумдарь; Д.Бадамдаш (Politology, 2023)
Power is one of the primary research subjects of academic disciplines such as political science, sociology and psychology and still is at the core of further research efforts of social sciences. In recent years, power, its effects and main factors that influence power have been examined and researched from the perspectives of political and social psychology disciplines. This research describes power, nonconscious priming of the feeling, stereotype, responsibility, as well as correlation of power and personal characteristics using methods of interview, experiment, test and computer test. The research involves respondents through systematic sampling of among people with different power levels. Collected data is analyzed through factor analysis to determine main effect of key influencing factors and interaction effect among them.